Rhizosphere legacy of leaf-diseased rice and its impact on next generation - Jobert, Léa; Vicheth, Vichny; Czernic, Pierre; Suong, Malyna; Béna, Gilles; Moulin, Lionel (Frontiers in Microbiology, 2025)
Plants interact continuously with the surrounding soil microbiota, shaping and being shaped by these communities over time, termed as the plant-soil feedback (PSF). As a result, plants can leave a biological imprint in the soil that affects the performance of subsequent plants, a phenomenon termed the soil-borne legacy. In this study, we investigated how the rhizosphere microbiota of rice plants exhibiting (or not) foliar disease symptoms in a Cambodian field was modified and influenced subsequent generation of plants. Based on a visual assessment of foliar symptoms, we collected and mixed the rhizospheres of plants classified as “diseased” or “healthy,” respectively. These mixed rhizospheres were then used to sow new rice plants in controlled conditions, which were subsequently challenged with Xanthomonas oryzae pv. oryzae. Phenotypic analyses revealed that plants grown in the rhizosphere microbiota collected from diseased field plants were smaller, yet displayed smaller symptoms to foliar pathogens compared to those grown in the microbiota of healthy plants. Amplicon sequencing of roots and rhizospheres from field samples confirmed that diseased and healthy plants harbored distinct microbial communities. A dysbiotic rhizosphere was found to be present in leaf-diseased plants, in contrast to healthy ones. These differences were also detectable in the composite rhizosphere mixes, and persisted in the rhizospheres of a new generation of rice plants grown in these soils. This suggests a microbiota-driven legacy, wherein the health status of the previous generation shapes the microbial environment and influences plant phenotype in terms of growth and defense. Our results support the idea that leaf-diseased plants condition their rhizosphere microbiota thus influencing plant phenotype in the next generation. Understanding the impact of disease-induced microbial legacy on next generation plant phenotype is crucial for developing microbiome-based crop protection strategies.